2020
DOI: 10.3389/fonc.2020.554165
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of Tumor Immune Microenvironment and Relevant Genes in Hepatocellular Carcinoma Identifies Potential Prognostic Significance

Abstract: Background: The tumor immune microenvironment (TIME) is an external immune system that regulates tumorigenesis. However, cellular interactions involving the TIME in hepatocellular carcinoma (HCC) are poorly characterized. Methods: In this study, we used multidimensional bioinformatic methods to comprehensively analyze cellular TIME characteristics in 735 HCC patients. Additionally, we explored associations involving TIME molecular subtypes and gene types and clinicopathological features to construct a prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…T cells follicular helper, T cells regulatory Tregs, and M0 macrophages were significantly increased in the high-risk group according to our results. Another study concluded that T cells follicular helper and M0 macrophages were unfavorable prognostic markers ( 30 ), which is corroborated herein. As is known, Tregs form an important part of the tumor immunosuppressive microenvironment.…”
Section: Discussionsupporting
confidence: 87%
“…T cells follicular helper, T cells regulatory Tregs, and M0 macrophages were significantly increased in the high-risk group according to our results. Another study concluded that T cells follicular helper and M0 macrophages were unfavorable prognostic markers ( 30 ), which is corroborated herein. As is known, Tregs form an important part of the tumor immunosuppressive microenvironment.…”
Section: Discussionsupporting
confidence: 87%
“…The increase of Macrophages M0 is signi cantly correlated with OS and tumor stage of HCC [32]. Macrophages M0 can stimulate the production of TAM and Kupffer cells in the presence of carcinogenic factors, thereby inhibiting the progression of HCC caused by immunity [33]. This may be related to the malignant behavior of the highly expressed genes from our research and analysis.…”
Section: Discussionmentioning
confidence: 65%
“…However, current HCC immunotherapy still faces challenges, such as uncertainty in efficacy, numerous adverse events, and drug resistance even after initial patient benefits (Byun et al 2017 ; Sharma et al 2017 ). Previous studies have shown that the TME is closely related to the growth and development of HCC (Tahmasebi Birgani and Carloni 2017 ; Chen et al 2020 ). Thanks to the tremendous development of bioinformatics and high-throughput technology, cancer genomics research has been greatly facilitated.…”
Section: Discussionmentioning
confidence: 99%